Perlindungan Hukum Kekayaan Intelektual Komunal terhadap Obat Tradisional Jamu sebagai Pengetahuan Tradisional - Nurul Fitriani; Adi Sulistiyono (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The knowledge of medicine and treatment, also known as Jamu, is one of the most important areas of Traditional Knowledge. It is widespread among indigenous peoples and local communities, and is an integral part of the communal rights held by indigenous peoples. Almost all indigenous peoples have developed knowledge about plants for various purposes, especially for medicine. The use of biodiversity as an ingredient in medicinal herbs has been a common practice in Indonesia for centuries. The question that arises is whether the knowledge of Jamu has received adequate protection from the government againts the rights of indigenous peoples related to Traditional Knowledge. This is the focus of the author attention in this discussion. This research discusses the regulation of communal intellectual property in the legal framework used to protect the knowledge of traditional herbal medicine, and how the effectiveness of legal protection of communal intellectual property on traditional herbal medicine knowledge. The purposes of this study is to determine the legal protection of traditional knowledge and analyze the positive legal regulations. This research method used by researchers is the normative juridical approach method. The results of the research conducted by the author in this thesis can be concluded that Traditional Protection on Jamu needs to be protected in accordance with the concept of protection of Philipus M. Hadjon, namely by means of preventive protection and repressive protection.